Amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide and preparation method and application thereof

By preparing amorphous boron-phosphorus co-doped cobalt-molybdenum sulfides, the performance deficiencies of CoMoS4 supercapacitor and DMFC anode catalysts were solved, achieving high specific capacitance and excellent catalytic MOR performance, suitable for supercapacitor and DMFC applications.

CN121306799APending Publication Date: 2026-01-09ZHONGYUAN ENGINEERING COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511401287.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-28
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing CoMoS4 supercapacitor electrode materials and direct methanol fuel cell anode catalysts suffer from low specific capacity, poor conductivity, and poor structural stability. Furthermore, there are few reports on the use of CoMoS4 as anode catalysts in DMFCs, and the catalytic mechanism of MOR is unclear.

Method used

The amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide (BP-CoMoS4) was prepared by hydrothermal reaction and vacuum oven treatment to form an amorphous structure, expose more active sites, and improve conductivity and catalytic performance.

Benefits of technology

This technology improves the specific capacitance and rate performance of supercapacitors, enhances the catalytic activity and stability of DMFC anode catalysts, achieves efficient electrochemical reactions and long-term stability, and utilizes inexpensive materials that are easy to apply on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121306799A_ABST
    Figure CN121306799A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of energy storage and conversion, discloses amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide as well as a preparation method and application thereof, and aims to solve the technical problem of relatively poor electrochemical performance of CoMoS4. The preparation method comprises the following steps: adding cobalt salt, molybdenum salt, urea and boron phosphate into deionized water to obtain a solution A; foamed nickel is placed in the solution A, and a boron-phosphorus co-doped cobalt-molybdenum precursor is obtained through a hydrothermal reaction; and placing the boron-phosphorus co-doped cobalt-molybdenum precursor in an aqueous solution of a vulcanizing agent, and carrying out a secondary hydrothermal reaction to obtain BP-CoMoS4. Boron-phosphorus co-doping can promote formation of an amorphous region structure, more active sites are exposed, and the conductivity of the CoMoS4 material is improved. The amorphous BP-CoMoS4 is low in price, simple and convenient to prepare and easy to apply and industrialize on a large scale, and a new strategy is provided for developing high-performance bimetallic sulfide which is simultaneously suitable for a supercapacitor and an alkaline DMFC anode catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of energy storage and conversion, and particularly relates to a supercapacitor electrode material and a direct methanol fuel cell anode catalyst. Background Technology

[0002] Supercapacitors, due to their high power density, fast charge / discharge speed, long cycle life, and safety, have become a promising energy storage device. However, compared with commercial lithium batteries, supercapacitors have lower energy density, limiting their widespread application. Supercapacitors mainly consist of electrode materials, electrolytes, separators, and current collectors. Improving the specific capacitance of the electrode materials and extending the operating voltage of the supercapacitor are effective ways to increase its energy density. Furthermore, direct methanol fuel cells (DMFCs) are devices that utilize the methanol oxidation reaction (MOR) for energy conversion, offering advantages such as high energy conversion efficiency and energy density, and near-zero emissions. Commonly used anode catalysts in DMFCs are Pt and its alloys; however, Pt's high cost and resource scarcity, coupled with its susceptibility to intermediate products (CO), make it problematic. ads The poisoning of DMFCs, which reduces their catalytic activity and stability, limits their commercial application. Therefore, it is essential to develop high-performance non-precious metal materials for use as DMFC anode catalysts.

[0003] Transition metal sulfides, especially bimetallic transition metal sulfides (such as CoMoS4), are favored due to their excellent electrochemical activity and multiple redox couples (Co... 2+ / Co 3+ Mo 4+ / Mo 6+ CoMoS4 is used as an electrode material for supercapacitors. However, CoMoS4 still has some shortcomings, such as low intrinsic conductivity and poor structural stability, resulting in poor rate performance and cycle stability. Strategies to improve the performance of CoMoS4 supercapacitors include: (1) Composite method: Combining CoMoS4 with graphene or graphene-like materials. Literature (J. Energy Storage, 2024, 100, 113722) shows that after CoMoS4 is combined with graphitized nitrogen carbide, the rate performance and cycle stability are good at 1 mV s. -1 The specific capacitance reached 3675 F g. -1 However, at 100 mV s -1 The specific capacitance at that time was only 90 F g -1 (2) Interface engineering method: constructing heterojunction structures with other materials. Reference (J. Mater. Sci. Technol., 2025, 228, 155-171) shows that amorphous / crystalline heterojunction materials constructed from CoMoS4 and NiS2 exhibit high performance at 1 mA cm⁻¹. -2The specific capacitance reached 1341 mC cm⁻¹ -2 (3) Morphology control method: CoMoS4 with flower-like, needle-like, rod-like and hollow structures was prepared. Literature (Electrochim. Acta, 2020, 337, 135824) shows that hollow concave CoMoS4... x Box in 1 A g -1 The specific capacitance at that time was 1589 F g. -1 20 A g -1 The specific capacitance reached 1122 F g. -1 .

[0004] Although CoMoS4 has made some progress in the field of supercapacitors, the following problems still exist in its preparation and application: CoMoS4 has a low specific capacitance when used as an electrode material in supercapacitors. Furthermore, there are few reports on the use of CoMoS4 as an anode catalyst in DMFCs, and the catalytic MOR mechanism of CoMoS4 remains unclear. Therefore, developing an electrode material with a simple preparation method that is suitable for both supercapacitors and DMFC anode catalysts remains an unsolved technical challenge. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention proposes an amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide, its preparation method, and its applications.

[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows: A method for preparing an amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide (BP-CoMoS4) comprises the following steps: (1) Add a certain amount of cobalt salt, molybdenum salt, urea and boron phosphate to deionized water and stir to form solution A. Transfer solution A into a high-pressure reactor lined with polytetrafluoroethylene and add treated nickel foam. Perform hydrothermal reaction at 140-180℃ for 4-10 h. After cooling to room temperature, wash with deionized water and anhydrous ethanol respectively, and then place in a vacuum oven at 60-80℃ for 6-8 h to obtain boron-phosphorus co-doped cobalt-molybdenum precursor.

[0007] (2) Add a certain amount of sulfiding agent to deionized water and mix evenly to obtain solution B; transfer solution B into a high-pressure reactor lined with polytetrafluoroethylene and add the boron-phosphorus co-doped cobalt-molybdenum precursor obtained in step (1). Perform hydrothermal reaction at 140-180℃ for 4-8 h. After cooling to room temperature, wash with deionized water and anhydrous ethanol respectively, and then place in a vacuum oven at 60-80℃ for 6-8 h to obtain BP-CoMoS4, i.e., amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide.

[0008] In step (1) above, the molar ratio of cobalt salt, molybdenum salt and urea is 1:(0.5-1):6.

[0009] In step (1) above, each cm 2 Nickel foam requires 0.02-0.08 mmol of cobalt salt and 0.0025-0.01 mmol of boron phosphate.

[0010] The nickel foam treated in step (1) above refers to the nickel foam that needs to be ultrasonically cleaned for 10-20 minutes in sequence with 0.5-1 M hydrochloric acid, ethanol and deionized water.

[0011] Furthermore, in step (1) above, the cobalt salt is at least one of cobalt nitrate, cobalt sulfate and cobalt chloride, and the molybdenum salt is sodium molybdate or ammonium molybdate.

[0012] In step (2) above, each cm 2 Nickel foam requires 0.025-0.1 mmol of sulfiding agent.

[0013] Furthermore, the vulcanizing agent in step (2) above is thioacetamide or sodium sulfide.

[0014] Amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide was prepared using the above-described preparation method.

[0015] The above-mentioned amorphous boron-phosphorus co-doped cobalt-molybdenum sulfides are used in supercapacitors or direct methanol fuel cells.

[0016] Furthermore, the application in direct methanol fuel cells refers to its application in the alkaline DMFC anode reaction.

[0017] The beneficial effects of this invention are: (1) The amorphous BP-CoMoS4 material of the present invention uses an inexpensive boron phosphate in its preparation process to achieve boron-phosphorus co-doping and form an amorphous structure. The amorphous structure can expose more active sites, increasing the adsorption of electrolytes; in addition, boron-phosphorus co-doping can improve the conductivity of CoMoS4 material and provide additional pseudocapacitance, thereby improving the specific capacitance and rate performance of supercapacitors. Among them, the BP-CoMoS4 material at 1 A g -1 The specific capacitance can reach as high as 3008.4 F g. -1 20 A g -1 The capacitance retention rate was 52.1%.

[0018] (2) The amorphous BP-CoMoS4 material of this invention, with boron doping promoting the adsorption and activation of methanol and phosphorus doping weakening the adsorption of intermediate products and promoting their timely oxidation, releases active sites for subsequent electrochemical reactions, thereby improving the catalytic activity and long-term stability of MOR. Specifically, BP-CoMoS4 achieves 10 mA cm⁻¹ in 1 M KOH + 0.5 M CH₃OH solution. -2 The required voltage for the current density is 1.329 V (vs. RHE), and the current density retention rate after continuous operation for 12 hours at 1.524 V (vs. RHE) is as high as 82.1%.

[0019] (3) The amorphous BP-CoMoS4 described in this invention is a multifunctional material that exhibits excellent supercapacitor and catalytic MOR performance and can be applied in the fields of supercapacitors and DMFC.

[0020] (4) The amorphous BP-CoMoS4 material described in this invention does not contain any precious metals, is inexpensive, easy to prepare, and is easy to apply and industrialize on a large scale. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 The X-ray diffraction (XRD) patterns of the materials obtained in Example 1 and Comparative Examples 1-3 are shown.

[0023] Figure 2 The images are scanning electron microscope (SEM) images of the materials obtained in Example 1 and Comparative Examples 1-3; wherein, (a) BP-CoMoS4; (b) B-CoMoS4; (c) P-CoMoS4; and (d) CoMoS4.

[0024] Figure 3 The image shows a transmission electron microscope (TEM) image of the material obtained in Example 1.

[0025] Figure 4 The graph shows a comparison of the supercapacitor performance of the materials obtained in Examples 1-3 and Comparative Example 3 in 1 M KOH; where (a) the scan rate is 50 mV / s. -1 (a) Cyclic volt-ampere (CV) curves at current density of 1 A g; (b) Current density of 1 A g -1(c) Constant current charge-discharge (GCD) curves; (d) Relationship between specific capacity and current density curves; (e) Electrochemical impedance spectroscopy (EIS) curves.

[0026] Figure 5 The graph shows a comparison of the supercapacitor performance of the materials obtained in Example 1 and Comparative Examples 1-3 in 1 M KOH; where (a) the scan rate is 50 mV / s. -1 CV curve at time; (b) Current density of 1 A g -1 (c) GCD curve; (d) EIS curve.

[0027] Figure 6 The graph shows a comparison of the catalytic performance of the materials obtained in Example 1 and Comparative Examples 1-3 in a 1 M KOH + 0.5 M CH3OH solution for MOR; where (a) the scan rate is 50 mV s. -1 (a) CV curve at a scanning speed of 5 mV / s; (b) CV curve at a scanning speed of 5 mV / s -1 (c) Linear sweep current-voltage (LSV) curve at 1.424 V (vs. RHE) voltage; (d) Timing current (it) curve at 1.524 V (vs. RHE) voltage. Detailed Implementation

[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] The foamed nickel used in this invention was purchased from Huaxiong Environmental Protection Metal Materials, and its dimensions are 1.5 mm (thickness) * 300 mm * 1000 mm.

[0030] Example 1 The preparation method of the amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide in this embodiment includes the following steps: (1) 0.25 mmol Co(NO3)3·6H2O, 0.25 mmol Na2MoO4, 1.5 mmol urea and 0.03 mmol boron phosphate were added to 20 mL of deionized water and stirred to form solution A. Solution A was transferred to a high-pressure reactor lined with polytetrafluoroethylene and nickel foam (2 cm × 3 cm) that had been ultrasonically cleaned for 15 min with 0.5 M hydrochloric acid, ethanol and deionized water in sequence was added. The mixture was hydrothermally reacted at 160℃ for 8 h. After cooling to room temperature, it was cleaned with deionized water and anhydrous ethanol respectively, and then placed in a vacuum oven at 60℃ for 8 h to obtain boron-phosphorus co-doped cobalt-molybdenum precursor.

[0031] (2) Add 0.3 mmol of thioacetamide to 20 mL of deionized water and stir to form solution B. Transfer solution B into a high-pressure reactor lined with polytetrafluoroethylene and add the boron-phosphorus co-doped cobalt-molybdenum precursor prepared in step (1). React hydrothermally at 160℃ for 6 h. After cooling to room temperature, wash with deionized water and anhydrous ethanol respectively, and then place in a vacuum oven at 60℃ for 8 h to obtain amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide, denoted as BP-CoMoS4.

[0032] Example 2 The preparation method of the amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide in this embodiment includes the following steps: (1) 0.25 mmol Co(NO3)3·6H2O, 0.25 mmol Na2MoO4, 1.5 mmol urea and 0.015 mmol boron phosphate were added to 20 mL of deionized water and stirred to form solution A. Solution A was transferred into a high-pressure reactor lined with polytetrafluoroethylene and nickel foam (2 cm × 3 cm) that had been ultrasonically cleaned for 15 min with 0.5 M hydrochloric acid, ethanol and deionized water in sequence was added. The mixture was hydrothermally reacted at 160℃ for 8 h. After cooling to room temperature, it was cleaned with deionized water and anhydrous ethanol respectively, and then placed in a vacuum oven at 60℃ for 8 h to obtain boron-phosphorus co-doped cobalt-molybdenum precursor.

[0033] (2) Add 0.3 mmol of thioacetamide to 20 mL of deionized water and stir to form solution B. Transfer solution B into a high-pressure reactor lined with polytetrafluoroethylene and add the boron-phosphorus co-doped cobalt-molybdenum precursor prepared in step (1). React hydrothermally at 160℃ for 6 h. After cooling to room temperature, wash with deionized water and anhydrous ethanol respectively, and then place in a vacuum oven at 60℃ for 8 h to obtain boron-phosphorus co-doped cobalt-molybdenum sulfide, denoted as BP-CoMoS4.

[0034] Example 3 The preparation method of the amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide in this embodiment includes the following steps: (1) 0.25 mmol Co(NO3)3·6H2O, 0.25 mmol Na2MoO4, 1.5 mmol urea and 0.06 mmol boron phosphate were added to 20 mL of deionized water and stirred to form solution A. Solution A was transferred into a high-pressure reactor lined with polytetrafluoroethylene and nickel foam (2 cm × 3 cm) that had been ultrasonically cleaned for 15 min with 0.5 M hydrochloric acid, ethanol and deionized water in sequence was added. The mixture was hydrothermally reacted at 160℃ for 8 h. After cooling to room temperature, it was cleaned with deionized water and anhydrous ethanol respectively, and then placed in a vacuum oven at 60℃ for 8 h to obtain boron-phosphorus co-doped cobalt-molybdenum precursor.

[0035] (2) Add 0.3 mmol of thioacetamide to 20 mL of deionized water and stir to form solution B. Transfer solution B into a high-pressure reactor lined with polytetrafluoroethylene and add the boron-phosphorus co-doped cobalt-molybdenum precursor prepared in step (1). React hydrothermally at 160℃ for 6 h. After cooling to room temperature, wash with deionized water and anhydrous ethanol respectively, and then place in a vacuum oven at 60℃ for 8 h to obtain boron-phosphorus co-doped cobalt-molybdenum sulfide, denoted as BP-CoMoS4.

[0036] Example 4 The preparation method of the amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide in this embodiment includes the following steps: (1) 0.25 mmol Co(NO3)3·6H2O, 0.125 mmol Na2MoO4, 1.5 mmol urea and 0.03 mmol boron phosphate were added to 20 mL of deionized water and stirred to form solution A. Solution A was transferred to a high-pressure reactor lined with polytetrafluoroethylene and nickel foam (2 cm × 3 cm) that had been ultrasonically cleaned for 15 min in sequence with 0.5 M hydrochloric acid, ethanol and deionized water was added. The mixture was hydrothermally reacted at 160℃ for 8 h. After cooling to room temperature, it was cleaned with deionized water and anhydrous ethanol respectively, and then placed in a vacuum oven at 60℃ for 8 h to obtain boron-phosphorus co-doped cobalt-molybdenum precursor.

[0037] (2) Add 0.3 mmol of thioacetamide to 20 mL of deionized water and stir to form solution B. Transfer solution B into a high-pressure reactor lined with polytetrafluoroethylene and add the boron-phosphorus co-doped cobalt-molybdenum precursor prepared in step (1). React hydrothermally at 160℃ for 6 h. After cooling to room temperature, wash with deionized water and anhydrous ethanol respectively, and then place in a vacuum oven at 60℃ for 8 h to obtain boron-phosphorus co-doped cobalt-molybdenum sulfide, denoted as BP-CoMoS4.

[0038] Example 5 The preparation method of the amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide in this embodiment includes the following steps: (1) 0.5 mmol Co(NO3)3·6H2O, 0.5 mmol Na2MoO4, 3 mmol urea and 0.06 mmol boron phosphate were added to 30 mL of deionized water and stirred to form solution A. Solution A was transferred to a high-pressure reactor lined with polytetrafluoroethylene and nickel foam (2 cm × 3 cm) that had been ultrasonically cleaned with 1 M hydrochloric acid, ethanol and deionized water for 5 min was added. The mixture was hydrothermally reacted at 180℃ for 4 h. After cooling to room temperature, it was cleaned with deionized water and anhydrous ethanol respectively, and then placed in a vacuum oven at 80℃ for 6 h to obtain the boron-phosphorus co-doped cobalt-molybdenum precursor.

[0039] (2) Add 0.6 mmol of thioacetamide to 30 mL of deionized water and stir to form solution B. Transfer solution B into a high-pressure reactor lined with polytetrafluoroethylene and add the boron-phosphorus co-doped cobalt-molybdenum precursor prepared in step (1). React hydrothermally at 180℃ for 4 h. After cooling to room temperature, wash with deionized water and anhydrous ethanol respectively, and then place in a vacuum oven at 80℃ for 6 h to obtain boron-phosphorus co-doped cobalt-molybdenum sulfide, denoted as BP-CoMoS4.

[0040] Example 6 The preparation method of the amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide in this embodiment includes the following steps: (1) 0.125 mmol Co(NO3)3·6H2O, 0.125 mmol Na2MoO4, 0.75 mmol urea and 0.015 mmol boron phosphate were added to 15 mL of deionized water and stirred to form solution A. Solution A was transferred into a high-pressure reactor lined with polytetrafluoroethylene and nickel foam (2 cm × 3 cm) that had been ultrasonically cleaned for 20 min with 0.75 M hydrochloric acid, ethanol and deionized water in sequence was added. The mixture was hydrothermally reacted at 140℃ for 10 h. After cooling to room temperature, it was cleaned with deionized water and anhydrous ethanol respectively, and then placed in a vacuum oven at 70℃ for 8 h to obtain boron-phosphorus co-doped cobalt-molybdenum precursor.

[0041] (2) Add 0.15 mmol of thioacetamide to 15 mL of deionized water and stir to form solution B. Transfer solution B into a high-pressure reactor lined with polytetrafluoroethylene and add the boron-phosphorus co-doped cobalt-molybdenum precursor prepared in step (1). React hydrothermally at 140℃ for 8 h. After cooling to room temperature, wash with deionized water and anhydrous ethanol respectively, and then place in a vacuum oven at 70℃ for 7 h to obtain boron-phosphorus co-doped cobalt-molybdenum sulfide, denoted as BP-CoMoS4.

[0042] Comparative Example 1 The preparation method of β-CoMoS4 in this comparative example is as follows: (1) 0.25 mmol Co(NO3)3·6H2O, 0.25 mmol Na2MoO4, 1.5 mmol urea and 0.03 mmol boric acid were added to 20 mL of deionized water and stirred to form solution A. Solution A was transferred into a high-pressure reactor lined with polytetrafluoroethylene and nickel foam (2 cm × 3 cm) that had been ultrasonically cleaned for 15 min with 0.5 M hydrochloric acid, ethanol and deionized water in sequence was added. The mixture was hydrothermally reacted at 160℃ for 8 h. After cooling to room temperature, it was cleaned with deionized water and anhydrous ethanol respectively, and then placed in a vacuum oven at 60℃ for 8 h to obtain boron-doped cobalt-molybdenum precursor.

[0043] (2) Add 0.3 mmol of thioacetamide to 20 mL of deionized water and stir to form solution B. Transfer solution B into a high-pressure reactor lined with polytetrafluoroethylene and add the boron-doped cobalt-molybdenum precursor prepared in step (1). React hydrothermally at 160℃ for 6 h. After cooling to room temperature, wash with deionized water and anhydrous ethanol respectively, and then place in a vacuum oven at 60℃ for 8 h to obtain boron-doped cobalt-molybdenum sulfide, denoted as B-CoMoS4.

[0044] Comparative Example 2 The preparation method of P-CoMoS4 in this comparative example is as follows: (1) 0.25 mmol Co(NO3)3·6H2O, 0.25 mmol Na2MoO4, 1.5 mmol urea and 0.03 mmol sodium hypophosphite were added to 20 mL of deionized water and stirred to form solution A. Solution A was transferred to a high-pressure reactor lined with polytetrafluoroethylene and nickel foam (2 cm × 3 cm) that had been ultrasonically cleaned for 15 min with 0.5 M hydrochloric acid, ethanol and deionized water in sequence was added. The mixture was hydrothermally reacted at 160℃ for 8 h. After cooling to room temperature, it was cleaned with deionized water and anhydrous ethanol respectively, and then placed in a vacuum oven at 60℃ for 8 h to obtain phosphorus-doped cobalt-molybdenum precursor.

[0045] (2) Add 0.3 mmol of thioacetamide to 20 mL of deionized water and stir to form solution B. Transfer solution B into a high-pressure reactor lined with polytetrafluoroethylene and add the phosphorus-doped cobalt-molybdenum precursor obtained in step (1). React hydrothermally at 160℃ for 6 h. After cooling to room temperature, wash with deionized water and anhydrous ethanol respectively, and then place in a vacuum oven at 60℃ for 8 h to obtain phosphorus-doped cobalt-molybdenum sulfide, denoted as P-CoMoS4.

[0046] Comparative Example 3 The preparation method of CoMoS4 in this comparative example is as follows: (1) 0.25 mmol Co(NO3)3·6H2O, 0.25 mmol Na2MoO4 and 1.5 mmol urea were added to 20 mL of deionized water and stirred to form solution A. Solution A was transferred into a high-pressure reactor lined with polytetrafluoroethylene and nickel foam (2 cm × 3 cm) that had been ultrasonically cleaned for 15 min with 0.5 M hydrochloric acid, ethanol and deionized water in sequence was added. The mixture was hydrothermally reacted at 160℃ for 8 h. After cooling to room temperature, it was cleaned with deionized water and anhydrous ethanol respectively, and then placed in a vacuum oven at 60℃ for 8 h to obtain the cobalt-molybdenum precursor.

[0047] (2) Add 0.3 mmol of thioacetamide to 20 mL of deionized water and stir to form solution B. Transfer solution B into a high-pressure reactor lined with polytetrafluoroethylene and add the cobalt-molybdenum precursor obtained in step (1). React hydrothermally at 160℃ for 6 h. After cooling to room temperature, wash with deionized water and anhydrous ethanol respectively, and then place in a vacuum oven at 60℃ for 8 h to obtain cobalt-molybdenum sulfide, denoted as CoMoS4.

[0048] Implementation Results Example The crystal structure and morphology, supercapacitor performance, and catalytic performance of the materials prepared in the examples and comparative examples were tested, and the specific results are as follows: (1) Crystal structure and morphology The XRD patterns of the CoMoS4-based materials obtained in Example 1 and Comparative Examples 1-3 are as follows: Figure 1 As shown. Comparing it with standard card PDF# 04-0850, the diffraction peaks at diffraction angles 2θ = 44.7°, 52.1°, and 76.6° correspond to the (111), (200), and (220) crystal planes of Ni, respectively. Apart from this, the XRD pattern showed no other obvious diffraction peaks, indicating that the CoMoS4-based materials obtained in Examples 1 and Comparative Examples 1-3 have weak crystallinity or are amorphous.

[0049] SEM images of the CoMoS4-based materials obtained in Example 1 and Comparative Examples 1-3 are shown below. Figure 2 As shown. From Figure 2 It can be observed that pure CoMoS4 exhibits a spherical structure composed of interwoven nanosheets. For example... Figure 2 As shown in a-2c, after heteroatom doping, the resulting BP-CoMoS4, B-CoMoS4, and P-CoMoS4 materials exhibit a fluffy, flower-like structure, and the resulting nanosheets are wrinkled. The specific surface area of ​​the three materials increases compared to before doping, which is beneficial for increasing the contact area with the electrolyte, thereby improving the performance of supercapacitors and the catalytic MOR performance.

[0050] TEM images of the BP-CoMoS4 material obtained in Example 1 are as follows: Figure 3 As shown. From Figure 3 It can be observed that BP-CoMoS4 is a porous material. No obvious lattice fringes are found in the high-resolution TEM image, and no obvious diffraction rings appear in the selected diffraction rings, further indicating that BP-CoMoS4 has an amorphous structure.

[0051] (2) Performance of supercapacitors The CoMoS4-based materials obtained in Examples 1-3 and Comparative Examples 1-3 were used as electrode materials to test the performance of supercapacitors. The specific testing method was as follows: a three-electrode test system was assembled using the obtained CoMoS4-based material as the working electrode, a platinum sheet as the counter electrode, and an Hg / HgO electrode as the reference electrode. CV, GCD, and EIS tests were performed, with a 1 M KOH solution as the electrolyte.

[0052] The performance comparison of BP-CoMoS4 and CoMoS4 materials obtained in Examples 1-3 and Comparative Example 3 in 1 M KOH is shown in the figure below. Figure 4 As shown. In Figure 4 In step a, the BP-CoMoS4 material prepared with boron phosphate at a dosage of 0.03 mmol was tested at 50 mV / s. -1 The area under the CV curve is largest when the CV curve is in the specified state, while the area under the CV curve is smallest for pure CoMoS4 material, indicating that boron-phosphorus co-doping can improve the storage capacity of CoMoS4 material. Figure 4 In b, the GCD curves of the four CoMoS4-based materials showed good symmetry, indicating that the materials possess excellent electrochemical reversibility. Furthermore, the BP-CoMoS4 material prepared with 0.03 mmol of boron phosphate exhibited good electrochemical reversibility at 1 A g. -1 The charge-discharge time was the longest at [specific time value], while that of pure CoMoS4 material was the shortest, further verifying that boron-phosphorus co-doping can improve the storage capacity of CoMoS4 material. Figure 4 In c, the BP-CoMoS4 material prepared with boron phosphate at an amount of 0.03 mmol was used in 1 A g. -1 The specific capacitance at that time was 3008.4 F g. -1 20 A g -1 The specific capacitance at that time was 1567.3 F g. -1 The capacitance retention rate was 52.1%. The BP-CoMoS4 material prepared with 0.015 mmol of boron phosphate was used at 1 A g. -1 The specific capacitance at that time was 2362.5 F g. -1 20 A g -1 The specific capacitance at that time was 1138.8 F g. -1The capacitance retention was 48.2%. The BP-CoMoS4 material prepared with 0.06 mmol of boron phosphate was used at 1 A g. -1 The specific capacitance at that time was 1566.6 F g. -1 20 A g -1 The specific capacitance at that time was 596.3 F g. -1 The capacitance retention rate was 38.1%. CoMoS4 material at 1 A g... -1 The specific capacitance at that time was 1004.3 F g. -1 20 A g -1 The specific capacitance at that time was 471.0 F g. -1 The capacitance retention rate is 46.9%. Figure 4 In diagram d, the intersection of the Nyquist curve with the horizontal axis in the high-frequency region represents the internal resistance (R) of the solution. s ). R of four CoMoS4-based materials s The Nyquist curves of BP-CoMoS4 prepared with boron phosphate at concentrations of 0.87 Ω, 0.95 Ω, 0.89 Ω, and 0.98 Ω, respectively, and with a boron phosphate dosage of 0.03 mmol, show a stronger bias towards the vertical axis in the low-frequency region, indicating that this material has the fastest reaction kinetics. In summary, BP-CoMoS4 prepared with a boron phosphate dosage of 0.03 mmol exhibits the highest specific capacitance and capacitance retention; therefore, the optimal boron phosphate doping dosage is 0.03 mmol.

[0053] Example 1 and Comparative Examples 1-3: Performance comparison of supercapacitors for BP-CoMoS4, B-CoMoS4, P-CoMoS4, and CoMoS4 materials in 1 M KOH. Figure 5 As shown. In Figure 5 In a, the BP-CoMoS4 material at 50 mV s -1 The area under the CV curve is largest at time 1, followed by P-CoMoS4 and B-CoMoS4. The area under the CV curve of pure CoMoS4 is the smallest, indicating that heteroatom doping can improve the storage capacity of CoMoS4 material, and boron-phosphorus co-doping has the best effect. Figure 5 In b, the BP-CoMoS4 material is in 1 A g -1 The longest charge-discharge time was observed at the time of boron-phosphorus co-doping, followed by P-CoMoS4 and B-CoMoS4. Pure CoMoS4 material had the shortest charge-discharge time, further verifying that the BP-CoMoS4 material prepared by boron-phosphorus co-doping exhibits the best capacitance performance. Figure 5 In c, BP-CoMoS4 material at 1 A g -1 The specific capacitance at that time was 3008.4 F g. -1 20 A g-1 The specific capacitance at that time was 1567.3 F g. -1 The capacitance retention rate was 52.1%. B-CoMoS4 material at 1 A g... -1 The specific capacitance at that time was 1753.0 F g. -1 20 A g -1 The specific capacitance at that time was 970.6 F g. -1 The capacitance retention rate was 55.3%. The P-CoMoS4 material at 1 A g... -1 The specific capacitance at that time was 2475.3 F g. -1 20 A g -1 The specific capacitance at that time was 1277.2 F g. -1 The capacitance retention rate was 51.6%. CoMoS4 material at 1 A g... -1 The specific capacitance at that time was 1004.3 F g. -1 20 A g -1 The specific capacitance at that time was 471.0 F g. -1 The capacitance retention rate is 46.9%. Figure 5 In d, the R of BP-CoMoS4, B-CoMoS4, P-CoMoS4 and CoMoS4 materials s The specific capacitance values ​​were 0.87 Ω, 0.90 Ω, 0.88 Ω, and 0.98 Ω, respectively. Furthermore, the Nyquist curve of BP-CoMoS4 showed a stronger bias towards the vertical axis in the low-frequency region, indicating that BP-CoMoS4 exhibits the fastest reaction kinetics. In summary, the BP-CoMoS4 material prepared by boron-phosphorus co-doping exhibits the best supercapacitor performance. This is because boron-phosphorus co-doping promotes the formation of an amorphous structure, exposes more active sites, improves the conductivity of CoMoS4, and provides additional pseudocapacitance, thereby enhancing specific capacitance and rate performance.

[0054] (3) Catalytic performance The CoMoS4-based materials obtained in Example 1 and Comparative Examples 1-3 were used as electrode materials to test the electrocatalytic oxidation performance of methanol. The specific testing method was as follows: a three-electrode test system was assembled using the obtained CoMoS4-based material as the working electrode, a platinum sheet as the counter electrode, and an Hg / HgO electrode as the reference electrode. CV, LSV, EIS, and it tests were performed. The electrolytes were 1 M KOH and 1 M KOH + 0.5 M CH3OH solutions.

[0055] The comparison of the catalytic performance of BP-CoMoS4, B-CoMoS4, P-CoMoS4 and CoMoS4 materials obtained in Example 1 and Comparative Examples 1-3 in 1 M KOH + 0.5 M CH3OH solution for MOR is shown in the figure below. Figure 6As shown. Figure 6 a is 50 mV s -1 The CV curve at that time. According to... Figure 6 a. The peak current densities of BP-CoMoS4, B-CoMoS4, P-CoMoS4, and CoMoS4 materials at 1.724 V (vs. RHE) are 416.4, 270.0, 289.8, and 230.7 mA cm⁻¹, respectively. -2 This indicates that the BP-CoMoS4 material has the best catalytic MOR performance. Figure 6 b is 5 mV s -1 LSV curves at [time unspecified] (without iR compensation). The MOR values ​​of BP-CoMoS4, B-CoMoS4, P-CoMoS4, and CoMoS4 materials reached 10 mA cm⁻¹. -2 The voltages required for the current densities were 1.329, 1.358, 1.334, and 1.363 V (vs. RHE), indicating that the BP-CoMoS4 material requires the lowest voltage to catalyze MOR. Figure 6 c represents the EIS curve at a voltage of 1.424 V (vs. RHE). It can be observed that the charge transfer resistance of BP-CoMoS4 is significantly lower than that of the other three materials, indicating that BP-CoMoS4 exhibits the fastest reaction kinetics. Figure 6 d represents the it curve at a voltage of 1.524 V (vs. RHE). According to... Figure 6 d. The current density retention rates of BP-CoMoS4, B-CoMoS4, P-CoMoS4, and CoMoS4 materials after 12 hours of continuous operation were 82.1%, 70.8%, 76.3%, and 53.6%, respectively, indicating that BP-CoMoS4 material exhibits the best catalytic stability. In summary, BP-CoMoS4 material possesses the best catalytic activity and stability for MOR, which is attributed to the synergistic catalytic effect of boron-phosphorus co-doping. Boron doping promotes the adsorption and activation of methanol, while phosphorus doping weakens the adsorption of intermediate products, promotes their timely oxidation, and releases active sites for subsequent electrochemical reactions, thereby improving the stability and durability of BP-CoMoS4 material.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide, characterized in that, The steps are as follows: (1) Cobalt salt, molybdenum salt, urea and boron phosphate were added to deionized water and mixed evenly to obtain solution A; nickel foam was placed in solution A and subjected to hydrothermal reaction to obtain boron-phosphorus co-doped cobalt-molybdenum precursor; (2) The boron-phosphorus co-doped cobalt-molybdenum precursor obtained in step (1) is placed in an aqueous solution of a sulfiding agent and subjected to a second hydrothermal reaction to obtain an amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide.

2. The method for preparing amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide according to claim 1, characterized in that, In step (1), the molar ratio of cobalt salt, molybdenum salt and urea is 1:(0.5-1):

6.

3. The method for preparing amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide according to claim 2, characterized in that, In step (1), each cm 2 Nickel foam requires 0.02-0.08 mmol of cobalt salt and 0.0025-0.01 mmol of boron phosphate.

4. The method for preparing amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide according to claim 3, characterized in that, In step (1), the cobalt salt is at least one of cobalt nitrate, cobalt sulfate and cobalt chloride, and the molybdenum salt is sodium molybdate or ammonium molybdate.

5. The method for preparing amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide according to any one of claims 1-4, characterized in that, The hydrothermal reaction in step (1) is carried out at a temperature of 140-180℃ for 4-10 hours.

6. The method for preparing amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide according to claim 5, characterized in that, In step (2), each cm 2 Nickel foam requires 0.025-0.1 mmol of sulfiding agent.

7. The method for preparing amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide according to claim 6, characterized in that, The sulfiding agent in step (2) is thioacetamide or sodium sulfide.

8. The method for preparing amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide according to claim 7, characterized in that, The temperature of the secondary hydrothermal reaction in step (2) is 140-180℃, and the time is 4-8 h.

9. An amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide prepared by the preparation method according to any one of claims 1-4 or 6-8.

10. The application of the amorphous boron-phosphorus co-doped cobalt-molybdenum sulfide according to claim 9 in supercapacitors or direct methanol fuel cells.